Unwrapping Academic Advisement and Student Satisfaction in Higher Education in Jamaica: A Case of Two Private Institutions - Oneil N Madden; Johnson, Jaemar; Daley, Jason-Lee; Fearon, Leroy (Ilmu Inovasi Nusantara, 2025)
Academic advisement and student satisfaction are critical components of student success in higher educational institutions, and they help to determine graduation success rates. Across the world, universities are giving more attention to students’ overall university experience and how they can make it more favorable. However, academic advisement and student satisfaction are understudied in Jamaican and Caribbean contexts. This study hopes to bridge that gap by adding to the scarcity of literature. To achieve this, the researchers sought to ascertain students’ perceptions of academic advisement at their university, factors influencing student satisfaction, and how they can be improved. Data was obtained from 62 students from Northern Caribbean University and the University of the Commonwealth Caribbean via a Google Forms questionnaire with both open- and close-ended questions. Data was analyzed using content and thematic analyses. The findings show mixed views concerning students’ perceptions of academic advisement, with most views trending negatively due to lecturers' lack of effective communication. Significant factors that affect student satisfaction include efficient communication, quality teaching and emotionally intelligent faculty, flexible learning and payment plans, student support services, appropriate learning facilities, and opportunities for holistic development. To improve the situation, students recommend enhanced communication and responsiveness, improvement in academic advising and support and systematic issues, and enhanced student engagement and well-being. The study has implications for academic advising and student satisfaction frameworks and how technology can be leveraged to improve communication outcomes